Improving literacy by teaching morphemes - Nunes, T; Bryant, P (Routledge Taylor and Francis Group, 2006)
With reports from several studies showing the benefits of teaching young children about morphemes, this book is essential reading for anyone concerned with helping children to read and write. By breaking words down into chunks of meaning that can be analyzed as complete units rather than as strings of individual letters, children are better able to make sense of the often contradictory spelling and reading rules of English. As a result, their enjoyment of learning about words increases, and their literacy skills improve. Written by leading researchers for trainee teachers, practising teachers and interested parents, this highly accessible and innovative book provides sound, evidence-based advice and materials that can be used to help teach children about morphemes, and highlights the beneficial effects of this approach.